El secuestro : su repercusión en las creencias y en la estructura de relaciones en un grupo de familias antioqueñas (2003)
ABSTRACT: Kidnapping, a sociopolitical act of the internal conflict in Colombia, and its impact on the relations and paradigms of 32 Antioqueño families Department that occupies the first place in the country and the world with regards to this situation), was investigated in a multidimensional way. Such relations and paradigms were evaluated in a suposedly critical period, four to nine months after liberation. The objective was to describe the interactions and beliefs of families affected by kidnapping and its association with the alteration of balance and therapeutical needs of individuals and families. The instruments applied were: reflexive-collaborative interview, scale of vision of the world and genogram. The results indicated that families defined union as an essential part of their identity and as a belief proyected two to cultural values: money and religiosity. The structure of relations was very close and after captivity, the couple was more simmetrical, the father became closer to his children and jerarchy was more democratical. The religious practice and the negotiating skill strengthened. Finally, trust on the state diminished, since they felt they were abandoned by it. The majority faced kidnapping successfully, but 85% defined it negatively. 28% presented a certain subsystem tension: loss, explosion of vulnerabilities and closedness. Two significant associations were given: the relations with conflict or gaining distance, family treatment, and a low commitment with life and the individual.